Role of protein and hydrolysates before exercise - Tipton, K. D. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
Adaptations to exercise training are determined by the response of metabolic and molecular mechanisms that determine changes in proteins. The type, intensity, and duration of exercise, as well as nutrition, determine these responses. The importance of protein, in the form of intact proteins, hydrolysates, or free amino acids, for exercise adaptations is widely recognized. Exercise along with protein intake results in accumulation of proteins that influence training adaptations. The total amount of protein necessary to optimize adaptations is less important than the type of protein, timing of protein intake, and the other nutrients ingested concurrently with the protein. Acute metabolic studies offer an important tool to study the responses of protein balance to various exercise and nutritional interventions. Recent studies suggest that ingestion of free amino acids plus carbohydrates before exercise results in a superior anabolic response to exercise than if ingested after exercise. However, the difference between pre-and postexercise ingestion of intact proteins is not apparent. Thus, the anabolic response to exercise plus protein ingestion seems to be determined by the interaction of timing of nutrient intake in relation to exercise and the nutrients ingested. More research is necessary to delineate the optimal combination of nutrients and timing for various types of training adaptations. Protein and amino acid intake have long been deemed important for athletes and exercising individuals. Olympic athletes, from the legendary Milo to many in the 1936 Berlin Games, reportedly consumed large amounts of protein. Modern athletes may consume slightly less than these historical figures, yet protein is deemed extremely important by most. Protein is important as a source of amino acids for recovery from exercise and repair of damaged tissues, as well as for adaptations to exercise training, such as muscle hypertrophy and mitochondrial biogenesis.